(untitled) (Balneo and PRM Research Journal, 2024)
Abstract: Postraumatic rehabilitation represent a dynamic field, with specific protocols and technics. Our prospective study targets the tibial pilon fractures admitted in our clinic, to which a new treatment protocol was applied, consisting of two surgical steps, assesing in the end the results achieved at the discharge of the patient and later follow up. The study group consist of 196 patients (198 fractures), in the period 2019-2022. The average evaluation time was of 16 months. The most frequently applied osteosynthesis principle was staged osteosynthesis which consisted of first stage fibula plate osteosynthesis and external fixator tibia pilon, followed by minimally invasive or limited approach locked plate tibia pilon fixation. (64.14%) Olerud and Molander clinical score at more than one year after the last surgical intervention highlights good results: excellent results in the amount of 37% to 15% in the first lot, good results 52% to 29%, moderate success 7% to 39% and poor 4% to 17%. Two stage surgery protocol with external fixation in emergency and minimally invasive internal fixation with locked plate performed after the dissappearance of the local edema, as the second surgical step, allows anatomically correct articular reconstruction without skin complications, with decrease of arthitic late complications.